If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying Y = x + -5 Reorder the terms: Y = -5 + x Solving Y = -5 + x Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Simplifying Y = -5 + x
| 249=4x^2+32x-11 | | 8-d=d-6 | | 7+5j=6j | | Ax-y+z=6 | | -0.03x+0.11(x+16000)=2080 | | 5t+7r-15r= | | 3t-8=-2t+7 | | 18=3(v-13)-6 | | 5x+19+7x+98=213 | | 3t-8=-2the+7 | | 3t-8=-3 | | 5+4x=-1x | | 9h=-8+10h | | 8x-4=y | | 3(x+2)+23= | | 3x+7x-5x= | | 2(y-3)+5=3(x-1) | | 6(-5x+1)=-204 | | 0=1.5x-3.4 | | 2(710+1)= | | 3(-8+8x)=-192 | | (x-2)(x^2-2x+4)-x(x-3)(x+3)=26 | | 5q+-6q-p= | | 1410+2= | | 5(2t+3)=30-5t | | 0=9x^2+12x-3 | | 5x+23=x+3 | | g(5+7)= | | 3x-8=8x+6 | | log(3)0.63= | | 2(14+w)=52 | | =.5x^2-4x+12 |